2008
DOI: 10.1002/mnfr.200700182
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of polybrominated diphenyl ethers and hexabromocyclododecane in milk from Stockholm mothers, 1980–2004

Abstract: Environmental and human exposures to brominated flame retardants (BFR) have been of emerging concern since some BFR are persistent and bioaccumulative compounds. Among those, polybrominated diphenyl ethers (PBDE) have frequently been reported in low to high ng/g concentrations in human blood around the world while hexabromocyclododecane (HBCDD) only occasionally has been reported and then in the low ppb concentrations in human blood. The present study concerns PBDE congener and HBCDD concentrations in human mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 35 publications
(33 reference statements)
8
65
1
1
Order By: Relevance
“…In fact, also levels of BDE-153 in breast milk seem to have started to decrease from about year 2004 , and a biphasic curve could be seen for BDE-153 in milk when the whole period 1996-2010 is studied. A study of PBDEs in mother's milk from women in Stockholm (1980Stockholm ( -2004 (Fangstrom et al, 2008) showed decreasing levels of BDE-47 from about 1995, while the levels of BDE-153 and HBCD seemed to have stabilized but not decreased after year 2000. The observed similarity between trends for BDE congeners in serum and breast milk is indeed expected from the results of our present study showing strong correlations between the levels in these two matrices upon analysis of paired serumbreast milk samples in first-time mothers.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, also levels of BDE-153 in breast milk seem to have started to decrease from about year 2004 , and a biphasic curve could be seen for BDE-153 in milk when the whole period 1996-2010 is studied. A study of PBDEs in mother's milk from women in Stockholm (1980Stockholm ( -2004 (Fangstrom et al, 2008) showed decreasing levels of BDE-47 from about 1995, while the levels of BDE-153 and HBCD seemed to have stabilized but not decreased after year 2000. The observed similarity between trends for BDE congeners in serum and breast milk is indeed expected from the results of our present study showing strong correlations between the levels in these two matrices upon analysis of paired serumbreast milk samples in first-time mothers.…”
Section: Discussionmentioning
confidence: 95%
“…Hier zeigt sich von 1980 (< 0,1 ng/g Fett) bis 2004 (0,4 ng/g Fett) ein Anstieg der Konzentrationen in Muttermilchproben aus Stockholm [42]. Im Zeitraum von 1996-2006 lagen > 60 % der Proben (n = 335) aus Uppsala unterhalb der Bestimmungsgrenze (LOQ) von 0,2 ng/g Fett [43].…”
Section: Vorkommen In Der Muttermilchunclassified
“…For example, biomonitoring research showed that PBDE levels declined in Sweden after these chemicals were banned. 69 Such public health interventions and policies have the potential to improve health by decreasing exposure to toxic chemicals. The Centers for Disease Control and Prevention has a biomonitoring program that continues to raise public awareness and provides data for state and federal regulations and opportunities for public health actions.…”
Section: Resultsmentioning
confidence: 99%